Prevalence of hypertension and associated risk factors among petrol pump workers in Panvel city, Maharashtra: a cross-sectional study - Alok Ratna; Rakesh Kumar; Suparna Khera; Suhas M. Vishwambhar; Sunil V. Gitte (International Journal Of Community Medicine And Public Health, 2026)
Background: Hypertension is a major public health challenge and an important risk factor for cardiovascular diseases worldwide. Petrol pump workers are exposed to occupational and lifestyle factors that may predispose them to hypertension. This study aimed to determine the prevalence of hypertension and associated risk factors among petrol pump workers in Panvel city, Maharashtra. Methods: A cross-sectional study was conducted among 156 petrol pump workers aged 30 years and above in Panvel city, Raigad district, Maharashtra. Data were collected using a structured pre-tested questionnaire covering socio-demographic characteristics, occupational profile, dietary habits, tobacco and alcohol consumption, sleep pattern, and physical activity. Blood pressure was measured using standard procedures. Hypertension was defined as systolic blood pressure ≥140 mmHg and/or diastolic blood pressure ≥90 mmHg. Statistical analysis was performed using Chi-square test and odds ratios with 95% confidence intervals. Results: The overall prevalence of hypertension was 30.8% (48/156). Additional salt intake was significantly associated with hypertension. Long-term tobacco use (≥10 years) was associated with increased odds of hypertension. Occupational factors such as duration of employment, standing duration, and working hours were not significantly associated with hypertension. Conclusions: Nearly one-third of petrol pump workers were hypertensive. Additional salt intake was a significant risk factor for hypertension. Regular screening, dietary counselling, tobacco cessation services, and workplace-based lifestyle interventions are recommended for early detection and prevention of hypertension among petrol pump workers.